Introducing Warning labels as an Informative Intervention in the Consumption of Sugar Sweetened Beverages (SSBs): A Study of Young Adults in Urban Pakistan - Ahmed, Syeda Arisha (2020)
Packaged foods that contain high added-sugar content are found to contribute to higher risks of chronic non-communicable diseases (NCDs). This research focuses on Sugar Sweetened Beverages (SSBs) and the use of warning labels to reduce their consumption and purchase among young adults in Pakistan. The use of warning labels as an informative intervention has been proven successful in different countries as they provide concise and readily interpretable information to assist in fast and healthier consumption decision making. Text based warning labels outlining the detrimental effects of the consumption of SSBs were tested in an experimental survey which collected repeated measures of consumption and purchase before and after being exposed to the warning label (stimulus). Warning labels were shown to be statistically effective in reducing the likelihood of future consumption among the target cohort. Even though the sample did not show significant mean difference in the consideration of health implication before and after being exposed to the warning label, women were found to decrease their consumption more than men. The moderation effects of demographic variables such as education, age and gender in reducing consumption were found to be inconclusive. The use of the standard nutritional panels was found to be infrequent and uninterpretable by the sample population. This research therefore concludes that the use of warning labels can potentially reduce the consumption of SSBs which may subsequently lead to a decrease in chronic NCDs currently prevalent in Pakistan among the target cohort.